2003
DOI: 10.1038/sj.bjc.6600896
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic alterations in ovarian clear cell carcinoma detected by comparative genomic hybridisation

Abstract: Ovarian clear cell carcinoma (OCCC) accounts for a small but significant proportion of all ovarian cancers and is a distinct clinical and pathological entity. It tends to be associated with poorer response rates to chemotherapy and with a worse prognosis. Little is known about possible underlying genetic changes. DNA extracted from paraffin-embedded samples of 18 pure OCCC cases was analysed for genetic imbalances using comparative genomic hybridisation (CGH). All of the 18 cases showed genomic alterations. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 39 publications
0
27
0
1
Order By: Relevance
“…In particular, we observed gains of 8q, 17q, and 20q and losses on 9p, 11q, 16p/q, and 19p in >30% of the cell lines. Similar gains and losses in these regions with frequencies of >20% have previously been reported in ovarian clear cell carcinomas (9,11,12). Indeed, cell lines and phenotypically matched primary tumors have been shown to have similar molecular features (15), and the selection of optimal in vitro models of specific subtypes of primary cancers can be achieved by matching the aCGH and gene expression profiles of these tumors with those of the well-characterized cell lines (6,14).…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…In particular, we observed gains of 8q, 17q, and 20q and losses on 9p, 11q, 16p/q, and 19p in >30% of the cell lines. Similar gains and losses in these regions with frequencies of >20% have previously been reported in ovarian clear cell carcinomas (9,11,12). Indeed, cell lines and phenotypically matched primary tumors have been shown to have similar molecular features (15), and the selection of optimal in vitro models of specific subtypes of primary cancers can be achieved by matching the aCGH and gene expression profiles of these tumors with those of the well-characterized cell lines (6,14).…”
Section: Discussionmentioning
confidence: 73%
“…31). 12 The Ingenuity Pathway Analysis software 13 was used to analyze pathways and networks that were significantly enriched for genes whose expression correlated with copy number gains/amplifications and losses in ovarian clear cell carcinoma cell lines. The list of genes overexpressed when gained or amplified and down-regulated when lost were independently mapped to networks and canonical pathways available in the Ingenuity database and ranked by score.…”
Section: Translational Relevancementioning
confidence: 99%
See 1 more Smart Citation
“…The accumulated evidence from a variety of disciplines indicates that clear cell carcinoma also has several distinct cytogenetic, molecular genetic, and gene expression alterations when compared to other more common surface epithelial neoplasms. 8,[25][26][27][28] Not surprisingly, some of the differentially expressed genes found on mRNA expression studies of ovarian carcinoma fall into a proliferation cluster or cluster with genes encoding proteins involved in cell cycle progression. 26 Misregulation of the G1/S transition in the cell cycle is a fundamental component of the cellular transformation process and G1/S regulatory defects have been reported in a variety of human malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of a publicly available ovarian expression data set (Lu et al, 2004) revealed downregulation of C9orf14 in serous carcinomas relative to normal ovarian surface epithelium (P < 0.05). This observation, together with data describing the genetic loss of 9p21 in ovarian clear cell carcinomas (Dent et al, 2003), might also suggest that C9orf14 is involved in ovarian tumorigenesis.…”
Section: Resultsmentioning
confidence: 72%